Bridge the gap ? : programme book. Science and Humanity, conceived by Center for Contemporary Art, Kitakyushu. - CCA (Center for Contemporary Art), Kitakyushu; Behrend, Heike; Casti, John; Koolhaas, Rem; Latour, Bruno; Lim, William; Miyake, Akiko; Naesse, Arne; Obrist, Hans Ulrich; Rosenfield, Israel (Kitakyushu : CCA (Center for Contemporary Art), 2001)
Abramovic, Marina ; Ajiboyé Bamgboyé, Oladélé ; Ascott, Roy ; Boeri, Stefano ; Chu-joe Hsia ; Eliasson, Olafur ; Evans, Cerith Wyn ; Giggsberg, Anders ; Grigely, Joseph ; Höller, Carsten ; Koolhaas, Rem ; Latour, Bruno ; Lijn, Liliane ; Lim, William ; Lum, Ken ; Maharaj, Sarat ; Mau, Bruce ; Orozco, Gabriel ; Preiss, Jeff ; Rist, Pipilotti ; Tiravanija, Rirkrit ; Wang Jian Wei
Engels & Japans
The Conference Bridge the gap ?, CCA (Center for Contemporary Art) Kitakyushu, 24.07. - 27.07.2001
boek